The Service-Dominant Logic of Marketing and Marketing Ethics - Williams, John; Aitken, Robert (2011)
Abela and Murphy (J Acad Mark Sci 36(1):39–53, 2007) examined Service-Dominant (S-D) logic (Vargo and Lusch, J Mark 68(1):1–17, 2004) from the viewpoint of Marketing Ethics and concluded that whilst S-D logic does not have explicit ethical content, the Foundational Premises (FPs) of S-D logic do have implicit ethical content. They also conclude that what may be needed to make the implicit more explicit is the addition of another FP. The aim of this article is to explore whether S-D logic needs to be modified, if one wishes to construct a theoretical framework for analysis of Marketing that has ethical considerations fully integrated. We critically evaluate the claim that the FPs are inherently ethical and conclude that S-D logic should be modified. We offer an additional FP for consideration that relates to the role of personal and societal values in the co-creation of value. This FP is necessary because of the role that the ethical positions of actors play in exchange behaviour. However, it should be pointed out that whilst the article explores the ethical potential of S-D logic it does not privilege any particular ethical position or code. These concerns will be addressed in subsequent articles: the aim here is to establish the underlying rationale for including an explicit commitment to ethics in S-D logic.
Keywords: co-creation of value; Values; Ethics; Resource-Advantage theory; S-D logic